GROUP ACTIVITY THERAPY TO IMPROVE COGNITIVE FUNCTION OF THE ELDERLY BY GUESSING THE PICTURE - Riesmiyatiningdyah Riesmiyatiningdyah; Ninik Murtiyani; Kusuma Wijaya Ridi Putra (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2022)
The activity of providing Group Activity Therapy given to the elderly about Cognitive Therapy by guessing pictures for the elderly at UPT PMKS Mojopahit Mojokerto is one form of community service in the form of Activity Therapy activities which are expected to reduce problems that occur in the elderly, especially cognitive problems that are often experienced by Elderly. The implementation of the activity on April 22, 2022 took place at UPT PMKS Mojopahit Mojokerto. With the target is the elderly residents of UPT PMKS Mojopahit Mojokerto. Before the activity is carried out, there is a process of preparing activities for approximately 3 weeks before the activity is carried out, starting from determining the type of Activity Therapy to applying for permits to the relevant parties. As a form of evaluation, the activity was attended by 25 elderly people, the participants took part in the activity very enthusiastically, the Group Activity Therapy activity could run on time and smoothly.